Anatomical characterization, histochemistry and crystal analysis of the leaf blade of Mangifera indica L. - Sá, Rafaela Damasceno; Cavalcanti, Girllene da Silva; Santos, Deysielle Maria dos; Silva, Adolfo Santos da; Padilha, Rafael José Ribeiro; Alves, Luiz Carlos; Randau, Karina Perrelli (Journal of Environmental Analysis and Progress, 2019)
Mangifera indica L., popularly known as mangueira, is an important fruitful widely used in Brazilian traditional medicine for the treatment of diabetes, anemia, diarrhea, hemorrhoids, indigestion, asthma, bronchitis, flu, hypertension, rheumatism, disorders of the liver and for tumors. In order to expand the pharmacobotanical information about the species, this study aimed to perform the anatomical characterization, histochemistry and crystal analysis of the leaf blade of M. indica. For the anatomical characterization were used optical microscopy, polarization microscopy and scanning electron microscopy. Histochemical tests were performed to evidence the presence of metabolites and microchemical analyzes by dispersive energy spectroscopy were done to determine the elemental chemical composition of the crystals. The microscopic analysis allowed the identification of characters useful in the identification of the species, such as the presence of glandular trichomes in the leaf blade. Through histochemistry was evidenced the presence of phenolic compounds, lipophilic substances, lignin and starch in the leaf blade. The chemical nature of the crystals was determined to be calcium oxalate. The results contribute to the pharmacobotanical standardization of M. indica.